ABC Publishing Co. Ltd. : a case study of a company in the process of change. - Chan, Ying Lock. (2009)
This is a case study of ABC Publishing Co. Ltd., an established 25 year old publisher of travel guidebooks based in Singapore whose average copies per title sold plateaued five years ago and has been gradually falling since.